Exploring the Organizational Culture in Adult Day Services (ADS) and Its Effect on Healthcare Delivery in Taiwan. (13th February 2020) - Liou, Chih-Ling; Dellmann-Jenkins, Mary
Abstract : Studies conducted in nursing homes/hospitals have shown that organizational culture plays an important role in care delivery and group culture leads to better quality of care. To explore the organizational culture and care delivery in adult day services (ADS) centers in Taiwan, we used both quantitative and qualitative research methods. Quantitative data from the Competing Values Framework (CVF) assessment showed that the group culture was dominant at all three centers. Qualitative data from observation and staff interviews uncovered both group and nongroup cultural elements. The group cultural elements, such as flexible management, teamwork environment, and sharing the same values, contributed to good care; however, the nongroup cultural elements, such as the staff-centered view, hierarchy, and conflicts within the leadership, led to negative staff-staff and staff-clients interactions. Further research is needed to untangle the complexity between quality care delivery and organizational culture.